Tobacco Taxes and Smoking Bans Impact Differently on Obesity and Eating Habits - Davide Dragone; Francesco Manaresi; Luca Savorelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
Policy interventions aimed at affecting a specific behavior may also indirectly affect individual choices in other domains. In this paper we study the direct effect of tobacco excise taxes and smoking bans on smoking behavior, and the indirect effect on eating behavior and body weight. Using very detailed clinical data on individual health, smoking, and dietary habits, we show that antismoking policies are effective in reducing smoking, but their consequences on eating behavior dramatically depend on the specific implemented policy. Increasing excise taxes on tobacco decreases body weight and caloric intake, and it improves the quality of eaten food. Smoking bans, instead, do not significantly affect body weight, although they impact on the diet composition. Smoking bans in restaurants induce a significant rise in the quality of food and in daily caloric intake. Conversely, smoking bans in bars negatively affect the quality of the daily diet, as individuals eat more fats and less fibers, and drink more alcohol and caffeine.
Keywords: I10; I18; 330